STEM-26. ASTROCYTIC SOX2+ CELLS RELAY IN NON-CANONICAL GLI SIGNALING TO FACILITATE MEDULLOBLASTOMA RELAPSE. (14th November 2022) - Swiderska-Syn, Marzena; Mir-Pedrol, Julia; Oles, Alexander; Babcock, Benjamin; Martin, Vanesa; Krieg, Carsten; Gershon, Timothy; McCrea, Heather; Rodriguez-Blanco, Jezabel
Abstract: Medulloblastoma is the most common malignant pediatric brain tumor. Despite the fair efficacy of current treatment approaches, 30 % of patients with medulloblastoma relapse. Cells expressing the stemness biomarker SRY (sex determining region Y)-box 2 (SOX2) are known to play key roles in sustaining medulloblastoma growth, providing chemo-resistance, and driving tumor relapse. It is therefore critical to elucidate the underlying mechanisms that propagate these cells and ensure therapies to target them. Single cell sequencing analyses revealed the existence of a subset of astrocyte-like SOX2 + cells expressing biomarkers indicative of SHH signaling activation. Intriguingly, such SOX2 + cells were not affected by the upstream SHH inhibitor vismodegib. Using SOX2 + enriched cultures, we observed that astrocyte-like SOX2 cells not only express SHH effectors, but require GLI signaling to proliferate, and that GLI is activated in a non-canonical and MYC dependent manner. Importantly, in vivo inhibition of SHH signaling downstream of SMO depleted the vismodegib resistant SOX2 + cell pool, while reduced the ability of residual medulloblastoma tissues to engraft in vivo . Our data show that in medulloblastoma, a subset of SOX2 + tumor cells rely on non-canonical GLI signaling to propagate, and emphasizes the importance of using therapies that deplete SOX2 + cells to prevent tumor recurrence.